(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Recurrent aphthous stomatitis (RAS), commonly called "canker sores," is a perplexing oral condition characterized by the recurrent development of painful aphthous ulcers on non-keratinized oral mucous membranes. This condition poses a significant challenge to patients and healthcare professionals due to its uncertain etiology. The study aims to evaluate the efficacy of millets in the management oral ulcers (aphthous). Millets are formulated in the form of an oral gel as gels are low cost and easily administered. Three types of millets are used for the study- Pearl millet, Foxtail millet and Finger millet. Millets are evaluated for anti-microbial and anti-inflammatory activity due to their rich content of essential vitamins, minerals, and antioxidants. The anti-microbial activity of the millets and the standard drug, Amoxicillin were observed and the zone of inhibition was calculated at 100, 300 and 500 mg/ml concentrations. The anti-inflammatory activity was assessed by calculating the % inhibition of protein denaturation using the absorbance value. Millets showed significant activities when compared with the standard drug. All these properties of millets and the chemical constituents heal mouth ulcers providing efficient drug delivery. Thus, these millets can be incorporated in the form of gel for the treatment of mouth ulcer.